Money, financial flows, and credit in the Soviet Union - Garvy, George (New York : Published for National Bureau of Economic Research [by] Ballinger, 1977)
This is a valuable addition to literature on Soviet finance. Garvy deserves our gratitude for having presented so much material in a readable volume of modest size. His account, while brief, is comprehensive; hardly an aspect of Soviet money, credit, and finance is omitted. Related topics, especially pricing, are included as well. Institutions and practices are put in perspective, and most important of all, rendered intelligible within the overall context of Soviet planning and management.
Includes index.
Includes bibliographical references: p. 204-218.
rpm 02/05/2018
Loans
Keywords: Finance; Money; Banks and banking; Credit